Time and Narrative Technique in Margaret Laurence's Manawaka Novels and A Bird in the House - Sinclair, Marie Lynne (My University, 1976)
The relation between time and narrative technique in The Stone Angel, A Bird in the House and The Diviners is the relation between content and form. Margaret Laurence states in her lecture "Gadgetry or Growing? ... Form and Voice in the Novel", that she has no interest in form for its own sake:
I am not concerned at all about trying forms and means of expression which are new simply for their own sake or for the sake of doing something different...l am concerned mainly, I think, with finding a form which will enable a novel to reveal itself...
(The Manawaka World of Margaret Laurence, p .129 )
The form of each of the three works that I have named is based on various uses of a flashback technique, and the form points to one of the most important themes in the works, which is that of the importance of an individual's past to the person she is in the present, and can become in the future. Laurence shows us over and over again that, as Morag, the most articulate of her narrators discovers, we have to go home again: "You Can't Go Home Again, said Thomas Wolfe. Morag wonders now if it may be the reverse which is true. You have to go home again, in some way or other." (The Diviners, p.248) The necessity of going home does not necessarily imply a physical journey to Manawaka, which is home for the narrators of the five works that I discuss. The important journey is the imaginative journey through time to a past that must be. relived and revalued until the traveller is content that he stands in a proper relation to his past. In my analysis of the relation of time to narrative technique, I attempt to demonstrate the importance of the novel's means of expression to what it expresses.
I have included A Jest of God and. The Fire-Dwellers because I see a similar treatment of time in them, even though the techniques of narration that Laurence uses in these two novels do not lend themselves to the same kind of discussion as do The Stone Angel, A Bird in the House and The Diviners. The five works, The Stone Angel, A Jest of God, The Fire-Dwellers, A Bird in the House and The Diviners, invite discussion as a group because they all have as either an important setting or a point of reference, the fictional town of Manawaka. They are also linked by a similar treatment of the theme of time.
Keywords: English Language and Literature; English Language and Literature